Pengaruh Instagrammable Interior Terhadap Kepuasan Pelanggan Di Rubeka Coffee Shop Batam - Diah Galuh Lestari; Dailami .; Wahyudi Ilham; Natal Olotua Sipayung (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
The development of social media, particularly Instagram, has driven many cafes to create attractive and Instagrammable interior designs to capture visitor’s attention. Aesthetic interiors now serve not only as decorative elements but also as part of a lifestyle and an indirect promotional medium. This phenomenon encouraged the researcher to examine the influence of Instagrammable interior design on customer satisfaction at Rubeka Coffee Shop Batam. This study employed a quantitative approach using the Structural Equation Modeling – Partial Least Square (SEM-PLS) method through the SmartPLS4 application, involving 100 respondents who were customers of Rubeka Coffee Shop Batam. The analysis results show that all indicators met the convergent validity test outer loading and AVE values > 0.5, and reliability tests with Cronbach’s Alpha and Composite Reliability values > 0.7. The R-Square value was 0.738, indicating that 73,8% of customer satisfaction is explained by Instagrammable interior design. Furthermore, the path coefficient value of 0.859, T-statistic of 21.066, and P-value of 0.000 confirm a positive and significant effect. This study emphasizes that an attractive and aesthetic interior design not only enhances the visual appeal of a space but also contributes significantly to customer satisfaction.